Core‐shell structured HZSM‐5@mesoSiO2 catalysts with tunable shell thickness for efficient n‐butane catalytic cracking. Issue 4 (6th January 2021) - Yang, Qingxin; Li, Yuming; Chen, Zhentao; Hu, Linxie; Li, Zhenye; Wang, Yajun; Zhao, Zhen; Xu, Chunming; Jiang, Guiyuan
Abstract: A series of core‐shell HZSM‐5@mesoSiO2 with tunable shell thickness from 10 to 70 nm was prepared and studied for n ‐butane catalytic cracking. With introducing of SiO2 shell, the catalytic performance of HZSM‐5@mesoSiO2 was largely enhanced, and n ‐butane conversion rate per Al site reached to 2.43 min −1 over HZSM‐5@mesoSiO2 (1:4) at 675°C which is nearly twice to that of HZSM‐5 (1.34 min −1 ). The diffusion property of n ‐butane over as‐prepared sample was quantified by measuring the diffusional time constants using zero length column chromatography technique (ZLC). Combining with chemical reaction kinetic analysis, the quantitative relationship between diffusion property and catalytic performance was effectively established for the first time in n ‐butane catalytic cracking. Positive linear correlation between diffusional time constant ( D / R 2 ) and n ‐butane conversion rate per Al site could be found, which confirms that diffusion enhancement by hierarchical structure is an effective strategy to improve the activity of HZSM‐5 in catalytic cracking.